The Effect of Voice Rest on the Outcome of Phonosurgery for Benign Laryngeal Lesions: Preliminary Results of a Prospective Randomized Study. (May 2015) - Kiagiadaki, Devora; Remacle, Marc; Lawson, George; Bachy, Vincent; Van der Vorst, Sebastien
Objectives: According to the literature, voice rest following phonosurgery, as recommended in clinical practice, varies between 3 and 7 days. However, up until now, no randomized trials have been published comparing voice rest of short versus long duration. Methods: This is an ongoing prospective randomized study, comparing strict voice rest of 5 versus 10 days on the voice following phonosurgery. Thirty-one elective patients operated on for benign laryngeal lesions were randomized. They completed pre- and postoperative assessments, including perceptual voice quality (Grade, Roughness, Breathiness, Asthenia, Strain, Instability scale), Voice Handicap Index total score, and voice analysis with both acoustic and aerodynamic measurements. Additional factors such as smoking, vocal abuse, reflux, and preoperative speech therapy were also taken into account. Results: Sixteen patients were randomized to follow 5 days' voice rest and 15 patients were randomized to 10 days' voice rest. Statistical analysis showed no significant differences in pre- or postoperative measurements between the 2 groups. However, multilinear regression analysis for the effect of voice rest duration on postoperative values showed a significant improvement in maximum phonation time (MPT) with 10 days' voice rest. Conclusions: Preliminary results show a benefit of prolonged voice rest (10 days' duration) on MPT.